The Distribution and Outcomes of the 21-Gene Recurrence Score in T1-T2N0 Estrogen Receptor-Positive Breast Cancer With Different Histologic Subtypes - Wang, Jun; He, Zhen-Yu; Dong, Yong; Sun, Jia-Yuan; Zhang, Wen-Wen; Wu, San-Gang (Frontiers in Genetics, 2018)
Background: The clinical value of 21-gene recurrence score (RS) in various breast cancer histologic subtypes is not well established. Aims: To assess the distribution and outcomes of the 21-gene RS among various T1-T2N0 estrogen receptor-positive breast cancer histologic subtypes. Methods: Using the Surveillance, Epidemiology and End Results database, we investigated the distribution and outcomes of the 21-gene RS among various breast cancer histologic subtypes between 2004 and 2015. The histologic subtypes with 200 or more cases were further analyzed. Results: We identified 83,665 patients including 8 histologic subtypes. The most common subtype was invasive ductal carcinoma not otherwise specified (IDC NOS) (77.9%), followed by lobular carcinoma NOS, mixed infiltrating duct and lobular carcinoma (IDC-L), mucinous adenocarcinoma, tubular adenocarcinoma, micropapillary ductal carcinoma, cribriform carcinoma NOS, and intraductal papillary adenocarcinoma with invasion with 10.8%, 7.7%, 2.1%, 0.6%, 0.3%, 0.2%, and 0.2%, respectively. The 5-year breast cancer specific survival (BCSS) was 98.8%, 98.8%, 98.9%, 99.6%, 100%, 100%, 100%, and 100%, respectively (P=0.011). Patients with IDC NOS (8.9%), micropapillary ductal carcinoma (8.8%), and intraductal papillary adenocarcinoma with invasion (8.2%) had significantly higher percentage of high-risk RS compared to other histologic subtypes (1.0-3.8%) (P<0.001). The mean RS was higher in IDC NOS, lobular carcinoma NOS, and IDC-L compared to other subtypes. In multivariate analysis, 21-gene RS was the independent prognostic factor in patients with IDC NOS (P<0.001), lobular carcinoma NOS (P<0.001), and IDC-L (P<0.001), patients with a higher RS was associated with poor BCSS. Conclusion: Our results demonstrate that there is a significant difference in distribution of 21-gene RS in T1-T2N0 estrogen receptor-positive breast cancer with different histologic subtypes. Long-term studies with larger series are needed to confirm the role of the 21-gene RS array in prognosis assessment and chemotherapy decision-making in special histologic subtypes with favorable prognosis.